Regular Exercise or Food Restriction, Which is Better in the Event of Heart Failure? An Approach to Oxidative Stress and Angiogenesis - Fatemeh Moradi; Alireza Imani; Abbas Shakoori; Mohammad Reza Vaez Mahdavi; Saman Mehrabi; Marjan Aghajani; Mohammad Molazem; Mahdieh Faghihi (The Society of Aging and Physical Activity (SAPA), 2016)
The aim of present study was to investigate whether food restriction combined with exercise training could attenuate the oxidative stress and promote angiogenesis in a rat model of heart failure. 50 male wistar rats weighing 250-300 g were randomly divided into 5 groups including: 1) sham; they were fed ad libitum food, n=10. 2) Heart failure group; 3) Exercise group; they run on a treadmill 5 days per week for 4 weeks, n=10. 4) Food restricted group; they were fed with 60% of their daily average food intake, n=10. 5) Food restricted plus exercise group; as well as feeding with 60% of their daily average food intake for 8 weeks and run on a treadmill 5 days for the 4 next weeks, n=10. Subcutaneous injection of isoproterenol (130 mg/kg) was used to induce experimental heart failure. Echocardiographic parameters were monitored. Plasma levels of malondialdehyde (MDA) and prooxidant/ antioxidant balance (PAB), as oxidative parameters were measured. In continue gene expression of angiogenic factors such as hypoxia inducible factor-1a (HIF-1a), vascular endothelial growth factor A (VEGFA) and endothelial nitric oxide synthase (eNOS) as well as histopathological examination were investigated. Isoproterenol-treated hearts showed lower functional indexes including LVEDd; Left Ventricular End Diastolic dimension (p<0.05), FS; Fractional Shortening (p<0.001), EF; Ejection Fraction, (p<0.001). In addition, significant increase in plasma levels of MDA (p<0.001) and PAB (p<0.001) were observed. Food restriction and exercise significantly improved all measured parameters. The protective role of food restriction and exercise training on myocardial damage was further confirmed by promoting the gene expression of angiogenic factors (p<0.001) in left ventricle and reducing the myocardial fibrosis (p<0.05). Our results suggest that combined food restriction with exercise training is superior to either therapy alone for improving functional indexes, strengthen balance of antioxidative defense system, as well as gene expression of angiogenic factors and decreasing myocardial fibrosis.